2017
DOI: 10.1111/evo.13299
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for intralocus sexual conflict over the optimal intake of nutrients for life span and reproduction in the black field cricketTeleogryllus commodus

Abstract: There is often large divergence in the effects of key nutrients on life span (LS) and reproduction in the sexes, yet nutrient intake is regulated in the same way in males and females given dietary choice. This suggests that the sexes are constrained from feeding to their sex‐specific nutritional optima for these traits. Here, we examine the potential for intralocus sexual conflict (IASC) over optimal protein and carbohydrate intake for LS and reproduction to constrain the evolution of sex‐specific nutrient reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 77 publications
(284 reference statements)
7
52
3
Order By: Relevance
“…Moreover, T. oceanicus are known to be plastic in their trait expression under different environmental pressures, as they are able to adjust the contribution to postmating traits according to the number of competitors in their environment (Gray & Simmons, 2013;Simmons & Lovegrove, 2017;Sloan, Lovegrove, & Simmons, 2018;Thomas & Simmons, 2009a. Rapkin et al (2017) have demonstrated that the regulated intake of protein and carbohydrate is heritable in T. commodus and that the regulation of protein intake is under stronger genetic control than carbohydrate intake; likewise, we observed a smaller variance on protein intake than carbohydrate intake in T. oceanicus ( Figure 5). It will be interesting to determine whether male crickets adjust the ratio of protein and carbohydrate intake in response to their social environment to optimize the expression of pre-and postmating sexual traits.…”
Section: Macronutrients Affect Trade-offs Between Pre-and Postmatinmentioning
confidence: 99%
“…Moreover, T. oceanicus are known to be plastic in their trait expression under different environmental pressures, as they are able to adjust the contribution to postmating traits according to the number of competitors in their environment (Gray & Simmons, 2013;Simmons & Lovegrove, 2017;Sloan, Lovegrove, & Simmons, 2018;Thomas & Simmons, 2009a. Rapkin et al (2017) have demonstrated that the regulated intake of protein and carbohydrate is heritable in T. commodus and that the regulation of protein intake is under stronger genetic control than carbohydrate intake; likewise, we observed a smaller variance on protein intake than carbohydrate intake in T. oceanicus ( Figure 5). It will be interesting to determine whether male crickets adjust the ratio of protein and carbohydrate intake in response to their social environment to optimize the expression of pre-and postmating sexual traits.…”
Section: Macronutrients Affect Trade-offs Between Pre-and Postmatinmentioning
confidence: 99%
“…Examples of active nutrient regulation can be found in a diversity of insect species, including predatory ground beetles (Anchomenus dorsalis; Jensen et al 2015), fruit flies (Drosophila melanogaster; Lee et al 2008;Jensen et al 2015), speckled roaches (Nauphoeta cinerea; South et al 2011;Bunning et al 2015Bunning et al , 2016, and field crickets (Teleogryllus commodus; Maklakov et al 2008;Rapkin et al 2017;Gryllus veletis, Harrison et al 2014). However, with the exception A. dorsalis, nutrient regulation in these species does not appear optimal for the expression of important phenotypic traits, such as reproduction (Lee et al 2008;Maklakov et al 2008;South et al 2011;Bunning et al 2015Bunning et al , 2016Jensen et al 2015;Rapkin et al 2017) and lifespan (Lee et al 2008;Maklakov et al 2008;Jensen et al 2015;Rapkin et al 2017). As traits frequently have different nutritional optima (e.g., Lee et al 2008;Maklakov et al 2008;Jensen et al 2015), it has been argued that this sub-optimal nutrient regulation may represent an attempt by individuals to balance the expression of multiple traits (Lihoreau et al 2015;Bunning et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One source of variation in nutrient intake that is likely to be important is the genotype of an individual. Indeed, studies on humans (e.g., Tanaka 2014), rats (e.g., Liu and Lloyd 2013), mice (e.g., Smith et al 2000), fruit flies (Reddiex et al 2013), and field crickets (Rapkin et al 2017) all indicate that the intake of macronutrients has a genetic basis. The predisposition to the deleterious effects of dietary overconsumption also appears to have a genetic basis that varies with the nutritional environment (van der Klaauw and Farooqi 2015), with genotype-by-diet interactions for weight gain and obesity being demonstrated in mice (Sutton et al 2006;Gordon et al 2008), D. melanogaster (Reed et al 2010), and humans (Qi and Cho 2008;Heianza and Qi 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Rapkin et al. () used quantitative genetics and dietary choice experiments utilizing the geometric framework to show that intralocus sexual conflict is likely not responsible for suboptimal nutrient regulation in T. commodus . The authors showed that protein and carbohydrate intake are highly heritable but differentially affect lifespan and reproductive output of the two sexes.…”
mentioning
confidence: 99%
“…The difference between preferred and optimal diet in T. commodus could also serve as a mechanism for reducing the fitness costs in offspring that Pischedda and Chippindale () reported. Rapkin et al.’s () findings show that much remains unknown about the underlying mechanisms of and interactions between IASC and sexual dimorphism.…”
mentioning
confidence: 99%